Dynamic Behavior of Materials, Volume 1 Proceedings of the 2018 Annual Conference on Experimental and Applied Mechanics - Kimberley, Jamie; Lamberson, Leslie Elise; Mates, Steven; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
Dynamic Behavior of Materials, Volume 1 of the Proceedings of the 2018 SEM Annual Conference & Exposition on Experimental and Applied Mechanics, the first volume of eight from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Experimental Mechanics, including papers on: Synchrotron Applications/Advanced Dynamic Imaging Quantitative Visualization of Dynamic Events Novel Experimental Techniques Dynamic Behavior of Geomaterials Dynamic Failure & Fragmentation Dynamic Response of Low Impedance Materials Hybrid Experimental/Computational Studies Shock and Blast Loading Advances in Material Modeling Industrial Applications.
Chapter 1.Error Analysis for Shock Equation of State Measurements in Polymers using Manganin Gauges -- Chapter 2.Ballistic Impact Experiments and Quantitative Assessments of Mesoscale Damage Modes in a Single-layer Woven Composite -- Chapter 3.A Novel Approach for Plate Impact Experiments to Obtain Properties of Materials under Extreme Conditions -- Chapter 4.Effect of the Ratio of Charge Mass to Target Mass on Measured Impulse -- Chapter 5.Fracture and Failure Characterization of Transparent Acrylic based graft Interpenetrating Polymer Networks (graft-IPNs) -- Chapter 6.Dynamic Crack Branching in Soda-lime Glass: An Optical Investigation using Digital Gradient Sensing -- Chapter 7.A Hybrid Experimental-Numerical Study of Crack Initiation and Growth in Transparent Bilayers Across a Weak Interface -- Chapter 8.Inelastic Behavior of Tungsten-Carbide in Pressure-Shear Shock Experiments beyond 20 GPa -- Chapter 9.Mechanical Response and Damage Evolution of High-Strength Concrete under Triaxial Loading -- Chapter 10.Heterodyne Diffracted Beam Photonic Doppler Velocimeter (DPDV) for Pressure-Shear Shock Experiments -- Chapter 11.An Optimization Based Approach to Design a Complex Loading Pattern Using a Modified Split Hopkinson Pressure Bar -- Chapter 12.Development of "Dropkinson" Bar for Intermediate Strain-rate Testing -- Chapter 13.Radial Inertia Effect on Dynamic Compressive Response of Polymeric Foam Materials -- Chapter 14.Keynote: Examining Material Response using X-ray Phase Contrast Imaging (40-min) -- Chapter 15.Historical Note: Machining, Strain Gages, and a Pulse-heated Kolsky Bar -- Chapter 16.Improved Richtmyer-Meshkov Instability Experiments for Very-High-Rate Strength & Application to Tantalum -- Chapter 17.Mechanical Characterization and Numerical Material Modeling of Polyurea -- Chapter 18.Full-Scale Testing and Numerical Modeling of Adhesively Bonded Hot Stamped Ultra-High Strength Steel Hat Sections -- Chapter 19.Mechanical Characterization of ZrO2 Rich Glass Ceramic -- Chapter 20.Microstructure Characterization of Electrodeposited Nickel Tested at High Strain Rates -- chapter 21.The Flow Stress of AM IN 625 Under Conditions of High Strain and Strain Rate -- Chapter 22.Proton Radiography of Reverse Ballistic Impacts -- Chapter 23.The Effect of ECAE on the Ballistic Response of AZ31 -- Chapter 24.Development of an Interferometer and Schlieren-based Measurement Technique for Resolving Cavitation Pressure Fields -- Chapter 25.Quasi-static and Dynamic Poisson's Ratio Evolution of Hyperelastic Foams -- Chapter 26.Revisit of Dynamic Brazilian Tests of Geomaterials -- Chapter 27.Interface Chemistry Dependent Mechanical Properties in Energetic Material using Nano-scale Impact Experiment -- Chapter 28.Optimization of an Image-based Experimental Setup for the Dynamic Behaviour Characterization of Materials -- chapter 29.High Strain Rate Response of Adhesively Bonded Fiber-Reinforced Composite Joints - A Computational Study to Guide Experimental Design -- Chapter 30.Pressure-Shear Plate Impact Experiments on Soda-Lime Glass at Pressures Beyond 20 GPa -- Chapter 31.Dynamic Mechanical Response of T800/F3900 Composite under Tensile and Compressive Loading -- Chapter 32.Experimental Investigation of Rate Sensitive Mechanical Response of Polyurea -- Chapter 33.Experimental Study on Dynamic Fracture Response of Al6063-T6 under High Rates of Loading -- Chapter 34.Ballistic and Material Tests and Simulations on Ultra-High Performance Concrete -- Chapter 35.Mechanical Behavior of Ta at Extreme Strain-rates -- Chapter 36.Constitutive Modeling of Polyamide Split Hopkinson Pressure Bars for the Design of a Pre-stretched Apparatus -- Chapter 37.Investigating the Mechanical and Thermal Relationship for Epoxy Blends -- Chapter 38.A Novel Auxetic Structure with Enhanced Impact Performances by Means Of Periodic Tessellation with Variable Poisson's Ratio -- Chapter 39.On the Response of Polymer Bonded Explosives at Different Impact Velocities -- Chapter 40.Meso-scale Dynamic Behavior of Cast Magnesium at High Strain Rate Loading -- Chapter 41.Energy Absorption Characteristics of Graded Foams Subjected to High Velocity Loading -- Chapter 42.Residual Structural Capacity of a High-Performance Concrete -- Chapter 43.Dynamic Mode II Fracture Response of PMMA Within an Aquatic Environment -- Chapter 44.An Image-Based Inertial Impact Test for the High Strain Rate Properties of Brittle Materials -- Chapter 45.An Image-Based Approach for Measuring Dynamic Fracture Toughness -- Chapter 46.The Effect of In-plane Properties on the Ballistic Response of Polyethylene Composites -- Chapter 47.Storage and Loss Moduli of Low-impedance Materials at kHz Frequencies -- Chapter 48.Effects of Pressure and Strain Rate on the Mechanical Behavior of Glassy Polymers -- Chapter 49.The Role of Texture on the Strain-Rate Sensitivity of Mg and Mg Alloy AZ31B -- Chapter 50.Shock Compaction of Al Powder Examined by X-Ray Phase Contrast Imaging -- Chapter 51.Compression Wave Profiles in Shock Loaded Polymer-metal Composites -- Chapter 52.High-Strain Rate Interlaminar Shear Testing of Fibre-Reinforced Composites Using an Image-Based Inertial Impact Test -- Chapter 53. Mechanical Behavior and Deformation Mechanisms of Mg in Shear Using In-Situ Synchrotron Radiation X-Ray Diffraction -- Chapter 54.Developing an Alternative to Roma Plastilina #1 as a Ballistic Backing Material for Body Armor Evaluation -- Chapter 55.IBI Test for High Strain Rate Tensile Testing of Adhesives -- Chapter 56.Modified Digital Gradient Sensors with Higher Measurement Sensitivity for Evaluating Stress Gradients in Transparent Solids -- Chapter 57.Quantitative Visualization of Sub-micron Deformations and Stresses at Sub-microsecond Intervals in Soda-lime Glass Plates -- Chapter 58.Microstructural Effects in the High Strain Rate Ring Fragmentation of Copper -- Chapter 59.Uncertainties in Low-Pressure Shock Experiments on Heterogeneous Materials -- Chapter 60.Effects of Liquid Viscosity on Wave Propagation Through Submerged Granular Media -- Chapter 61.Numerical Study of the Failure Mechanism of Ceramics during Low Velocity Impact Used In Protective Systems -- Chapter 62.Influence of High Strain Rate Transverse Compression on the Tensile Strength of Polyethylene Ballistic Single Fibers -- Chapter 63.The Utility of 3D Digital Image Correlation for Characterizing High-Rate Deformation -- Chapter 64.Characterization of Dynamic Deformation and Failure of Novel Light Weight Steel Alloy -- Chapter 65.Dynamic Fragmentation of MAX Phase Ti3SiC2 from Edge-On Impact Experiments -- Chapter 66.Application of High-speed DIC to Study Damage of Thin Membranes under Blast.
Keywords: Mechanics, Applied; Solids; Materials; Materials -- Analysis; Building materials; Solid Mechanics; Materials Engineering; Characterization and Analytical Technique; Structural Materials